ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN DAN PENJUALAN UD. PODO JOYO FARM - Seruni, Rose Putri Dwi; Astuti, Puji; Solikah, Mar’atus (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study is to evaluate the sales and inventory accounting information system at UD. Podo Joyo Farm Kediri. This research uses a qualitative approach with a descriptive type of research. Data mining methods with interviews, and observations as primary data, as well as secondary data from the researcher's documentation. Data analysis by data collection, data reduction, data presentation, and conclusions. With 5 informants based on their respective fields. The results of this study show that (1) Inside UD. Podo Joyo Farm Kediri has all procedures, documents, and functions that are in the sales and inventory accounting information system and all by theory, (2) In recording sales and inventory of goods still using manual methods and in the warehouse function there is a function conflict with the delivery function. From the results of this study, researchers recommend UD. Podo Joyo Farm Kediri for Functions must be carried out by their respective job desks so that work efficiency and employee performance can be maximized in terms of recording using modern computerized technology to facilitate performance and increase employee work effectiveness and efficiency. Therefore, recruitment is needed that considers skills in operating computers such as Microsoft Excel applications, google drives, spreadsheets, and other applications that can support recording UD logging. Podo Joyo Farm Kediri. The last is the use of documents that are listed in the theory of accounting information systems that have not been used in the company in the future can be used to support UD's credibility. Podo Joyo Farm Kediri.